Spectrum effect correlation of yangyin tongnao granules on cerebral ischemia-reperfusion injury rats - Yangyang Zhang; Li Yu; Jiehong Yang; Zhishan Ding; Yu He; Haitong Wan (Frontiers Media S.A., 2022)
Yangyin Tongnao Granules (YYTNG), as traditional Chinese medicine (TCM) compound preparation, have a good curative effect on cerebral ischemia-reperfusion injury. This study aimed to investigate the relationship between the active components of YYTNG in the plasma and the inflammatory response in cerebral ischemia-reperfusion injury rats. High-performance liquid chromatography (HPLC) was conducted to determine the fingerprints at different time points of middle cerebral artery occlusion (MCAO) rats after the administration of YYTNG at different times points. Enzyme-linked immunosorbent assay (ELISA) was performed to detect the levels of interleukin-18 (IL-18) and tumor necrosis factor-α (TNF-α) in the plasma of MCAO rats at different time points. The spectral-effect relationship between the YYTNG fingerprints and inflammatory indexes in vivo was established by combining three different mathematical models, grey correlation, multiple linear regression, and partial least-square method. The results revealed that each chromatographic peak in the HPLC of the plasma exhibited a certain correlation with the inflammatory index, in the following order: P2 >P6 >P5 >P1 >P3 >P4. Therefore, this study successfully established the spectrum-effect correlation of YYTNG on cerebral ischemia-reperfusion injury rats. The results provide a certain guiding ideology for the analyses of the relationship between fingerprints and the pharmacodynamics of TCM prescriptions.